Toxic ivory towers the consequences of work stress on underrepresented minority faculty - Zambrana, Ruth E. (Rutgers University Press, 2018)
"Toxic Ivory Towers seeks to document the professional work experiences of underrepresented minority (URM) faculty in U.S. higher education, and simultaneously address the social and economic inequalities in their life course trajectory. Ruth Enid Zambrana finds that despite the changing demographics of the nation, the percentages of Black and Hispanic faculty have increased only slightly, while the percentages obtaining tenure and earning promotion to full professor have remained relatively stagnant. Toxic Ivory Towers is the first book to take a look at the institutional factors impacting the ability of URM faculty to be successful at their jobs, and to flourish in academia. The book captures not only how various dimensions of identity inequality are expressed in the academy and how these social statuses influence the health and well-being of URM faculty, but also how institutional policies and practices can be used to transform the culture of an institution to increase rates of retention and promotion so URM faculty can thrive."-- Provided by publisher
Keywords: Minority college teachers -- United States.; Minorities in higher education -- United States.; Faculty integration -- United States.; Universities and colleges -- United States -- Faculty.; Discrimination in higher education -- United States.; Minorités dans l'enseignement supérieur -- États-Unis.; Universités -- États-Unis -- Corps enseignant.; Discrimination dans l'enseignement supérieur -- États-Unis.; EDUCATION / General; Discrimination in higher education; Faculty integration; Minorities in higher education; Minority college teachers; Universities and colleges -- Faculty; United States